Exploring the Impact of Societal Challenges on School Learner Development: An in-depth Analysis of Strategies for Effective Education Amidst Adversity - Muzamil Hussain AL Hussaini (PT FORMOSA CENDEKIA GLOBAL, 2023)
The contemporary educational landscape is often marred by a myriad of societal challenges that impede the holistic development of school learners. This research article delves into the intricate relationship between societal challenges and school learner development, examining how adversities such as poverty, inequality, violence, and cultural shifts influence the learning environment. Through a comprehensive literature review and empirical case studies, this article aims to elucidate the multifaceted impact of these challenges on educational outcomes and propose effective strategies for promoting learner development despite adversity. The study underscores the urgency of addressing societal issues to ensure equitable and optimal educational experiences for all learners